Solusi Alternatif Pengelolaan Sampah Rumah Tangga: Insinerator Sederhana sebagai Upaya Pencegahan ISPA pada Balita - Ratna Arifiana; Leila Nisya Ayuanda; Imam Prasetyo (Jurnal Pengabdian Ilmu Kesehatan, 2026)
Household waste that is not properly managed poses significant environmental and public health risks, particularly increasing the incidence of Acute Respiratory Infections (ARI) among children under five due to open waste burning and unhygienic environmental conditions. This community service program aimed to improve community knowledge and skills in household waste management through the utilization of a simple low-smoke incinerator as an alternative method to reduce waste while preventing ARI among young children. The program was conducted in Wuled Village, Pekalongan Regency, involving local community members as active participants. Educational sessions, practical demonstrations, and mentoring activities were implemented to strengthen participants’ understanding and encourage the adoption of appropriate waste management practices. Evaluation results showed substantial improvements in participants’ knowledge, attitudes, and motivation after the intervention. A total of 89% of participants demonstrated good knowledge, 80% showed positive attitudes, and 87% exhibited high motivation toward proper household waste management. Furthermore, participants successfully implemented household waste management practices using the introduced technology. These findings indicate that community-based assistance and practical education effectively promote sustainable household waste management behavior. The program also enhances community independence in maintaining environmental cleanliness, improving public health, and reducing the risk of ARI among children under five through environmentally friendly waste management practices.